On the Distribution of Determiners in Haitian Creole - Lumsden, John (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1989)
AbstractThe paper provides more precise data on the distribution of determiners in Haitian creole. It proposes that there are two independent constraints on the distribution of these functional categories. In Haitian, as in English, Hungarian, Turkish and Hebrew, a specific determiner is necessary to the realization of genitive Case. Moreover there is a general constraint on processing which forbids the insertion of two identical functional category signals in a linear sequence. This processing constraint can be seen in at least on other language (Fon).